The Impact of Augmented Reality (AR) and Virtual Reality (VR) on Virtual Banking and Consumer Experience - Pal, Sonia (Stallion Journal for Multidisciplinary Associated Research Studies, 2024)
AR and especially VR have significantly influenced virtual experiences, transforming the banking industry, particularly enhancing the consumer experience. These technologies enable banks to offer a tailored and engaging approach for consumers regarding the financial services they require, both in-person and online. Augmented reality enhances the banking experience by allowing information to be visually integrated into real-world spaces. In contrast, virtual reality offers a simulated environment where customers can interact with banking services and obtain their assistance. In the realm of virtual banking, the advantages for businesses include increased customer engagement, reduced operational expenses, and enhanced accessibility, particularly for those in remote areas, facilitated by the integration of AR and VR technologies. Additionally, they strengthen the security of the processes by utilising features such as biometric authentication and virtual consultations during transactions. However, the system's limitations could impede its acceptance, including significant implementation costs, technological challenges, and security risks. Consequently, integrating AR and VR is increasingly essential to reshape consumer expectations in banking services. Additional research remains needed to optimise the performance of these technologies for users and achieve more cost-effective outcomes.